Anticancer molecular mechanism of protocatechuic acid loaded on folate coated functionalized graphene oxide nanocomposite delivery system in human hepatocellular carcinoma - Buskaran, Kalaivani; Bullo, Saifullah; Hussein, Mohd Zobir; Masarudin, Mas Jaffri; Mohd Moklas, Mohamad Aris; Fakurazi, Sharida (Multidisciplinary Digital Publishing Institute, 2021)
Liver cancer is listed as the fifth-ranked cancer, responsible for 9.1% of all cancer deaths globally due to its assertive nature and poor survival rate. To overcome this obstacle, efforts have been made to ensure effective cancer therapy via nanotechnology utilization. Recent studies have shown that functionalized graphene oxide (GO)-loaded protocatechuic acid has shown some anticancer activities in both passive and active targeting. The nanocomposites’ physicochemical characterizations were conducted. A lactate dehydrogenase experiment was conducted to estimate the severity of cell damage. Subsequently, a clonogenic assay was carried out to examine the colony-forming ability during long-term exposure of the nanocomposites. The Annexin V/ propidium iodide analysis showed that nanocomposites induced late apoptosis in HepG2 cells. Following the intervention of nanocomposites, cell cycle arrest was ascertained at G2/M phase. There was depolarization of mitochondrial membrane potential and an upregulation of reactive oxygen species when HepG2 cells were induced by nanocomposites. Finally, the proteomic profiling array and quantitative reverse transcription polymerase chain reaction revealed the expression of pro-apoptotic and anti-apoptotic proteins induced by graphene oxide conjugated PEG loaded with protocatechuic acid drug folic acid coated nanocomposite (GOP–PCA–FA) in HepG2 cells. In conclusion, GOP–PCA–FA nanocomposites treated HepG2 cells exhibited significant anticancer activities with less toxicity compared to pristine protocatechuic acid and GOP–PCA nanocomposites, due to the utilization of a folic acid-targeting nanodrug delivery system.